“Middle age” as Prime Time of Human Life - Khusanova, Khayriniso; Sultanova, Lola; Khusanbaeva, Yulduz; Abduraximova, Dilnoza (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the socio-economic indicators of the population layer of the working age are studied. Psycho-physiological, socio-cultural characteristics of this layer are described in disciplines. The analysis of statistical data on the problem is presented. Also, sociological factors of socio-economic activity of the middle-aged population are revealed. This is based on the conclusions of empirical research conducted internationally in recent years. In the article, the population layer of the working age is interpreted as the main human Reserve in ensuring the sustainable development of society.